A taxonomic revision of the Stictopterinae (Lepidoptera, Noctuoidea, Noctuidae) in China - Qi, Feng; Wang, Ke; Xue, Dayong; Yang, Ding (Zootaxa, 2011)
The Stictopterinae from China are revised. Seven genera and forty species are reported from China. Five new species (Lo- phoptera hamata sp. nov., Lophoptera solealis sp. nov., Lophoptera acutiprocessa sp. nov., Lophoptera purpurfera sp. nov. and Lophoptera trigonoprocessa sp. nov.) are described. One genus and ten species are recorded from China for the first time. Nine misidentifications in Chen (1982b, 1991, 1999) are revised. The male genitalia of Lophoptera obliquilinea Prout, 1928 are described for the frist time. Descriptions for the subfamily, all genera, and new species in China are provided, as are keys to genera and species, diagnoses for all species, and illustrations of adults and genitalia.